POLA PENGEMBANGAN USAHA TANI PADA PONDOK PESANTREN AGROBISNIS DI SEKITAR KAWASAN HUTAN MERU BETIRI DI KABUPATEN JEMBER - Muharso, Urip; Subagiarta, I Wayan (Jurnal Sosial Ekonomi Pertanian, 2009)
This research is intended to identify the configuration of Islamic boarding schools at the most relevant areas or districts to start an implementation of farm management by industrial complex’s pattern at the surrounding of Meru Betiri area. This was analyzed by using Value of Location Quotient (LQ) method and Value of Dynamics Location Quotient. Meanwhile, Turla and Hawkins method was used to analyze the entrepreneurship ability of Islamic boarding schools of agribusiness. The analysis applied to formulate farm management development was Analytic Hierarchy Process (AHP). The research object was Islamic boarding schools of agribusiness which existed at the surrounding of Meru Betiri forest that covered Districts of Jenggawah, Ambulu, Tempurejo and Mumbulsari. The data collection method was limited survey supported by secondary data.Based on the analysis and discussion of the improvement effort of farm management at the surrounding of Meru Betiri area by applying Agroindustrial Complex, several conclusions could be drawn: (1) The areas (Districts) where the Islamic boarding schools were located that were mostly relevant for farm management efficiency examination of ‘Agro Complex’ were Districts of Mumbulsari and Ambulu. (2) The second alternative of strategy option i.e. developing farm management by the whole step-by-step Agro Complex’s pattern, was the responded option. The selected strategy option was consistent with the analysis result of ‘Turla and Hawkins’ method which indirectly explained that entrepreneurship ability of the boards of Islamic boarding schools was reliable to hold farm management by Agro Complex’s pattern that brought the appointed institutions to achieve Islamic boarding school of Agribusiness. (3) The strategy in applying agro-industrial complex as an attempt of farm management in Jember Regency should be focused on aspects of Human Resources, Marketing, Partnership and Economic Doers.Keywords: Agroindustrial Complex, Islamic boarding schools, Jember Regency